2018
DOI: 10.1021/acsanm.8b01476
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Doped 2D InSe for Spintronic Applications

Abstract: Using first-principles calculations based on density functional theory, we study the magnetic and electronic properties of hole-doped two-dimensional InSe. Our simulations reveal that although 2D InSe is intrinsically non-magnetic, a stable ferromagnetic phase appears for a wide range of hole densities. Interestingly, hole doping not only induces spontaneous magnetization but also half-metallicity, and hole-doped InSe, presenting one conducting and one insulating spin channel, could be highly promising for nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 59 publications
9
40
0
1
Order By: Relevance
“…[22][23][24] Thus, hole-doped 2D PtS 2 can be a ferromagnetic material, similar to other 2D metal chalcogenides. [6][7][8] Note that the inclusion of SOC preserves the sombrero shape VB and the subsequent van Hove singularity at the top of the VB and for the calculations of the magnetic and electronic properties of doped systems, this relativistic interaction is not included.…”
Section: Ferromagnetism In Hole-doped 2d Ptsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Thus, hole-doped 2D PtS 2 can be a ferromagnetic material, similar to other 2D metal chalcogenides. [6][7][8] Note that the inclusion of SOC preserves the sombrero shape VB and the subsequent van Hove singularity at the top of the VB and for the calculations of the magnetic and electronic properties of doped systems, this relativistic interaction is not included.…”
Section: Ferromagnetism In Hole-doped 2d Ptsmentioning
confidence: 99%
“…4,5 In addition, spontaneous magnetization has been predicted in monolayer metal chalcogenides, such as GaS, GaSe and InSe, upon hole doping. [6][7][8][9] Such magnetization arises from an exchange splitting of the electronic states at the valence band edge, where the density of states exhibits a sharp van Hove singularity, leading to the so-called Stoner instability.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers have been shown that monolayer InSe is a promising material for optoelectronics and photosensitive devices. In addition, 2D InSe engages for the application of bendable photodetectors with broadband response 23 , 2D ferromagnets 24 , and topological insulator 25 . The adsorption-induced magnetic behaviors on InSe monolayer was also reported on some studies 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Nano-devices based on two dimensional (2D) InSe had good ambient stability. 4 In addition, 2D InSe holds promise for the application of bendable photodetectors with broadband response, 5 2D ferromagnets, 6 excitonic dynamics, 7 magneto-optical effects 8 and topological insulator. 9 Recently, a new Janus-type monolayer MoSSe has been synthesized through the replacement of the S atoms at one side of monolayer MoS 2 by Se atoms.…”
mentioning
confidence: 99%